Dog Man. 8, Fetch 22 - Pilkey, Dav, 1966- (New York, N.Y. : Graphix, an imprint of Scholastic, 2019)
George and Harold create a new comic book hero in Dog Man, a crimefighter with the head of a police dog and the body of a policeman, who faces off against his archnemesis Petey the cat.
"Tree House Comix Proudly Presents."
Keywords: Comics (Graphic works).